IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN DESCRIPTIVE TEXT BY USING DICTO-COMP TECHNIQUE AT THE EIGHT GRADE STUDENTS OF MTsN PARE - sholikhah, novi nur (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Dicto-comp technique is the collaboration between dictation and composition. This study aimed to find out whether Dicto-comp technique can improve the students’ writing achievement in descriptive text at the eighth-grade students of MTsN Pare. The subject of this research was the VIII/H class. It consisted of 33 students, 16 males and 17 females. By using Classroom Action Research (CAR) as the research design, the researcher did interview, questionnaire, and observation checklist as data collecting method to get the result of the students’ activity. Moreover, to know the improvement of students’ writing achievement, the researcher used test and observed the test result by computing the average and the percentage of classroom success. The result of the study showed that more than 90% students were more active and interested in writing activity. Besides that, there is significant improvement in students’ writing achievement. In the first cycle, there were 54,55% students classified into success with the average score 73,03. Meanwhile, in the second cycle, there were 87,88% students classified into success with the average score 83,42. Therefore, it can be concluded that using Dicto-comp technique can improve the students’ writing achievement in descriptive text.